2018
DOI: 10.1155/2018/6765438
|View full text |Cite
|
Sign up to set email alerts
|

Fungal, Bacterial, and Archaeal Diversity in the Digestive Tract of Several Beetle Larvae (Coleoptera)

Abstract: Interpretation of how partnerships between fungi, bacteria, archaea, and insects are maintained through the life of the hosts is a big challenge within the framework of symbiosis research. The main goal of this work was to characterize the gut microbiota in larvae of several Coleoptera species using sequencing of the bacterial and archaeal 16S rRNA genes and fungal internal transcribed spacer (ITS) region. Thus, larvae with various food preferences, including Amphimallon solstitiale, Oryctes nasicornis, Cucuju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Nevertheless, a shotgun metagenomic analysis of the gut content of P. xylostella larvae identified Euryarchaeota DNA in very low proportions (Xia et al, ). Additionally, another recent study which used high‐throughput sequencing of bacterial and archaeal 16S rRNA genes reported notable levels of ammonia‐oxidizing Crenarchaeota in the larval hindgut of scarab beetles (Ziganshina et al, ). All the mentioned studies analysed DNA sequences, mostly through sequencing of archaeal 16S rDNA, thus targeting the taxonomic content of this domain but not its active functional profile.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a shotgun metagenomic analysis of the gut content of P. xylostella larvae identified Euryarchaeota DNA in very low proportions (Xia et al, ). Additionally, another recent study which used high‐throughput sequencing of bacterial and archaeal 16S rRNA genes reported notable levels of ammonia‐oxidizing Crenarchaeota in the larval hindgut of scarab beetles (Ziganshina et al, ). All the mentioned studies analysed DNA sequences, mostly through sequencing of archaeal 16S rDNA, thus targeting the taxonomic content of this domain but not its active functional profile.…”
Section: Discussionmentioning
confidence: 99%
“…They can help their host degrade the decaying wood and metabolize cellulose to promote larval digestion. Such as Ruminococcaceae are vital to degradation of lignocellulose [ 56 ]. Christensenellaceae and Lachnospiraceae are important for the degradation of plant material and cellulose catabolism [ 49 , 57 ], and Christensenellaceae is related to host health [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 It is worth mentioning that the similar bacterial phyla were observed in the various beetles (Coleoptera). 44,45 In this study, we investigated four silkworm strains that were reared on mulberry leaves, and the dominant bacteria in their intestines were also Cyanobacteria, Firmicutes, and Proteobacteria, indicating that the gut microbiota of silkworms reared on mulberry leaves is quite stable. The functions of the intestinal bacteria in the gut microbiota, as predicted by PICRUSt, showed that genetic differences between the silkworm strains with different articial diet ingestive habits, which were selected systematically or naturally occurring, did not have an impact on the functions of silkworms that were reared on mulberry leaves.…”
Section: Discussionmentioning
confidence: 99%